AN ANALYSIS OF ILLOCUTIONARY ACTS IN SPOKEN DIALOGS IN AN ENGLISH TEXTBOOK - Destra Wibowo Kusumo; Distya Kusuma Wardani (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2019)
The study intends: (1) to investigate the illocutionary acts and illocutionary forces; (2) to investigate the direct and indirect acts realized in the spoken dialogs in the textbook Bahasa Inggris SMA/ MA/ SMK/ MAK Kelas XII; and (3) to investigate whether the illocutionary forces fulfill the language functions in Basic Competence Curriculum 2013.This research was descriptive qualitative. The data was in the form of all utterances of the spoken dialogs. The main instrument is, hence, the researcher himself with the help of data sheet as the secondaryÂ  instrument. The data of this research were all the spoken dialogs. The data were then coded and analyzed by means of concept of illocutionary acts and the that of direct and indirect acts proposed by Searle (1979) with pragmatic identity method as proposed by Sudaryanto (1993/2009). Four types of illocutionary acts are found: representatives, expressives, directives, and commissives. Fourteen types of illocutionary forces are also found, namely stating an opinion, informing, reporting, explaining, describing, agreeing, greeting, leave-taking, stating surprise, thanking, sympathizing, commanding, requesting, suggesting, wishing, questioning, promising, and offering. Next, the direct acts dominate the utterances in the dialogs. From the research it is concluded that the textbook has fulfilled the language functions as stated in basic competence. Next, based on the findings of direct and indirect acts, the textbook has not realized the direct acts which influence the English natural conversations which lead to the authenticity.